Pengaruh Waktu Pemeraman Terhadap Daya Dukung Tanah Lempung Dan Lanau Yang Distabilisasi Dengan Menggunakan Kapur Pada Kondisi Rendaman (Soaked CBR) - Afrie, Fransiskus; Afriani, Lusmeilia; Iswan, Iswan (Universitas Lampung, 2017)
ABSTRACTThe soil layer is the bottom layer that has function to forward the load from construction on it. But not always the basic soil layer is able has function properly as the bearing capacity. The soil stabilization method with lime additive is an alternative that can be used in planning on a unstable soil construction. The aim of this research is to know the physical characters of clay soil in Sidodadi Asri area, Jati Agung subdistrict, South Lampung regency and the type of silt soil in Yosomulyo area, East Metro District, Metro City. And also to know the increase of the bearing capacity of both types of soil with variation of curing time of 7, 14 and 28 days. From the result of the physical character research and mechanical of original soil samples obtained so it can be concluded that land taken from Sidodadi Asri village classified as clay with high plasticity, while the soil from yosomulyo village is clay with low plasticity. And on the CBR test in the ideal soaking conditions with ideal lime content showed that the increase of CBR value in each soil type along with the increase of the curing duration of 2.8%, 4%, 6.4% and 10.2% in clay and 2, 2%, 3%, 3.6% and 6% in silt soils. This suggests that the ideal lime composite in addition to the curing duration gives a positive effect to increase bearing capacity soil or CBR value. Keywords: Lime, Stabilization, Clay and Silt Soil, Soaked CBR.